Application of Number Theory in Cryptography - Peranginangin, Andreas Perdamenta (PT Inovasi Pratama Internasional, 2024)
Life has changed in this era of technology. With technology, information can be searched easily and quickly, starting from the difficulty of finding information. Besides, people can easily store information in software or on the Internet. But you don't want this information to get out to anyone who doesn't want it. Therefore, data security is needed, which is applied using the science of cryptography, which uses material from number theory. This research will look at various cryptographic algorithms and processes for encrypting and decrypting data. This study uses library research or (library research). Library research involves gathering detailed information from numerous sources including literature, books, notes, journals, and other sources.